PENGGUNAAN STRAIN GAGE (LOAD CELL) UNTUK ANALISA TEGANGAN PADA PEMBEBANAN STATIK BATANG ALUMINIUM - Magga, Ramang (Jurnal MEKANIKAL, 2011)
This study aims to determine the effect of strain (vertical and horizontal directions) in analyzing the static loading stress on the aluminum rod. Research use aluminum rod with dimensions of 110 cm long and 30 cm, height 32.8 mm and 1.2 mm thick, two strain gage to the vertical direction and two for the horizontal direction. Giving the load from 500 grams to 10,000 grams is done. Results show that areas closed to vertical support (T2 = 26647375.311) has very high voltage compared to area in the middle (T1 = 2628679.465). Whereas, for the horizontal direction shows that the area near the support (T2 = 2629098.313) is much greater than in the middle pedestal (T1 =2659709.133).